Sex‐Based Differences in Outcomes Following Peripheral Artery Revascularization: Insights From VOYAGER PAD - Connie N. Hess; Iris Baumgartner; Sonia S. Anand; Mark R. Nehler; Manesh R. Patel; E. Sebastian Debus; Michael Szarek; Warren Capell; Eva Muehlhofer; Scott D. Berkowitz; Lloyd P. Haskell; Rupert M. Bauersachs; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background Despite high female prevalence of peripheral artery disease (PAD), little is known about sex‐based outcomes after lower extremity revascularization (LER) for symptomatic PAD. The effects of rivaroxaban according to sex following LER have not been fully reported. Methods and Results In VOYAGER PAD (Vascular Outcomes Study of ASA [acetylsalicylic acid] Along with Rivaroxaban in Endovascular or Surgical Limb Revascularization for Peripheral Artery Disease), low‐dose rivaroxaban versus placebo on a background of aspirin reduced the composite primary efficacy outcome of cardiovascular and limb events in patients with PAD undergoing LER. Unplanned index limb revascularization was prespecified and prospectively ascertained. The primary safety outcome was Thrombolysis in Myocardial Infarction major bleeding. Analyses of outcomes and treatment effects by sex were performed using Cox proportional hazards models. Among 6564 randomly assigned patients followed for a median of 28 months, 1704 (26.0%) were women. Among patients administered placebo, women were at similar risk for the primary efficacy outcome (hazard ratio [HR], 0.90; [95% CI, 0.74–1.09]; P=0.29) as men, while female sex was associated with a trend toward higher risk of unplanned index limb revascularization (HR, 1.18; [95% CI, 1.00–1.40]; P=0.0499). Irrespective of sex, effects of rivaroxaban were consistent for the primary efficacy outcome (P‐interaction=0.22), unplanned index limb revascularization (P‐interaction=0.64), and bleeding (P‐interaction=0.61). Women were more likely than men to discontinue study treatment (HR, 1.13; [95% CI, 1.03–1.25]; P=0.0099). Conclusions Among >1700 women with PAD undergoing LER, women and men were at similar risk for the primary outcome, but a trend for greater risk of unplanned index limb revascularization among women was observed. Effects of rivaroxaban were consistent by sex, though women more often discontinued treatment. Better understanding of sex‐based outcomes and treatment adherence following LER is needed. Registration URL: http://clinicaltrials.gov; Unique identifier: NCT02504216.